Developing an Understanding of The Sources of Some Graduate Students’ Perceptions of Academic Writing - Alhojailan, Ahmad I. (Universitas Pendidikan Indonesia, 2021)
An increasing number of Saudi students in American universities has generated a need to explore the Saudi students’ perceptions of academic writing and the sources of such perceptions. Further research can enable writing researchers and instructors to help Saudi students to be better writers in American contexts. This study, therefore, explored the sources of 12 Saudi graduate students' perceptions of academic writing. The findings collected from 12 semi-structured interviews revealed the sources of the participants’ perceptions of academic writing. These sources are the perceived effects of the participants’ professors, the perceived effects of their fields of study/occupations, the perceived effects of their peers, and the perceived effects of the Saudi culture. The findings suggest the creation of opportunities for writing practices that can help identify the origins of difficulties in academic writing and then help students overcome those difficulties and change the negative perceptions students have about academic writing. The findings also show that those sources are interrelated. A more in-depth study of student perceptions and their sources is needed because we need a broader picture of how such sources might interact with each other.